Meningkatkan Kreativitas Remaja Melalui Motivasi dan Pelatihan pada Remaja Komplek Pesona Pamulang Pondok Petir Depok - Ambar Widya; Diana Azwina; Oki Iqbal Khair (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
Creativity plays a major role in improving the welfare and quality of human life. Creativity for teenagers is needed because creativity bridges us towards a more advanced future. With creativity, young people can develop their ability to be entrepreneurs in order to open new jobs for the unemployed and young people who have no experience in business or other fields. In this case, we, a team of PKM lecturers from the Management Study Program, Pamulang University, have held a PKM activity with the theme